Genetic engineering of the branched fatty acid metabolic pathway of Bacillus subtilis for the overproduction of surfactin C14 isoform. Issue 7 (5th May 2017) - Dhali, Debarun; Coutte, François; Arias, Anthony Argüelles; Auger, Sandrine; Bidnenko, Vladimir; Chataigné, Gabrielle; Lalk, Michael; Niehren, Joachim; de Sousa, Joana; Versari, Cristian; Jacques, Philippe
Abstract: Surfactin, a lipopeptide produced by Bacillus subtilis, is one of the most powerful biosurfactants known. This molecule consists of a cyclic heptapeptide linked to a β‐hydroxy fatty acid chain. The isomery and the length of the fatty acid (FA) chain are responsible for the surfactin's activities. In this study, the gene codY, which encode for the global transcriptional regulator and the gene lpdV, located in the bkd operon ( lpdV, bkdAA, bkdAB and bkdB genes), which is responsible for the last step of the branched chain amino acid (BCAA) degradation in acyl‐CoA were deleted. The influence of these deletions on the quantitative and qualitative surfactin production was analysed. The surfactin production was quantified by RP‐HPLC and the surfactin isoforms were characterized using LC‐MS‐MS and GC‐MS analysis. The results obtained in the mutants showed an enhancement of surfactin specific production by a factor of 5.8 for the codY mutant and 1.4 for lpdV mutant. Moreover qualitative analysis of the lpdV mutant reveals that it mainly produced surfactin C14 isoform (2 fold more than the wild type) with linear FA chain. Complete analysis of the extracellular metabolites using 1 H quantitative NMR reveals a reduced production of acetoin in this mutant. This work demonstrates for the first time an original approach to overproduce specifically surfactin with C14 FA chain. Abstract : The surfactin produced by Bacillus subtilis consists of a cyclic heptapeptide linked to a β‐hydroxy fatty acid (FA) chain. The isomery and the length of the FA chain are responsible for the surfactin's activities. In this study, the gene codY (the global transcriptional regulator) and the gene lpdV (responsible for the branched chain amino acid (BCAA) degradation in branched chain fatty acid (BCFA)) were deleted. The results of these deletions showed an enhancement of surfactin specific production by a factor of 5.8 for the codY mutant and 1.4 for lpdV mutant. Moreover qualitative analysis of the lpdV mutant reveals that it mainly produced surfactin C14 isoform with straight FA chain. This work demonstrates for the first time an original approach to overproduce specifically surfactin with C14 FA chain.